2017
DOI: 10.1111/pce.12940
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory simulation of Arabidopsis seed dormancy cycling provides new insight into its regulation by clock genes and the dormancy‐related genes DOG1, MFT, CIPK23 and PHYA

Abstract: Environmental signals drive seed dormancy cycling in the soil to synchronize germination with the optimal time of year, a process essential for species' fitness and survival. Previous correlation of transcription profiles in exhumed seeds with annual environmental signals revealed the coordination of dormancy‐regulating mechanisms with the soil environment. Here, we developed a rapid and robust laboratory dormancy cycling simulation. The utility of this simulation was tested in two ways: firstly, using mutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 57 publications
2
57
0
Order By: Relevance
“…A clear distinction between primary and secondary dormancy is not always made regarding the effect of the maternal environment on dormancy levels (Footitt et al , ). We hypothesize that the difference of the maternal effect on primary and secondary dormancy (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A clear distinction between primary and secondary dormancy is not always made regarding the effect of the maternal environment on dormancy levels (Footitt et al , ). We hypothesize that the difference of the maternal effect on primary and secondary dormancy (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few factors to take into account when comparing these studies. Experimental differences include: (i) secondary dormancy induction conditions , with prolonged dark and cold conditions in the field versus dark and warm conditions in the laboratory (Cadman et al , ; Ibarra et al , ; Footitt et al , ); (ii) dormancy induction is slower and the time between sampling is longer in the field (months), compared with days or weeks in the laboratory; (iii) gradual changes in dormancy levels (in the field) compared with two states, non‐dormant and secondary dormant (in the laboratory) (Ibarra et al , ). Genes in which expression is reduced in secondary dormancy in laboratory experiments, such as the GA signalling related genes REPRESSOR OF GA ( RGA ), RGL1 , RGL2 , GA INSENSITIVE ( GAI ) are also significantly reduced in expression during dormancy induction in the field (Ibarra et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternating temperatures cycles are an environmental signal that relief seed dormancy and, consequently, contribute to define the dynamics of emergence of weed seedlings in the field (Benech‐Arnold et al, ). Unfortunately, this process has not been extensively studied in Arabidopsis ‐model‐seed system with recent exceptions (Footitt, Ölçer‐Footitt, Hambidge, & Finch‐Savage, ; Topham et al, ). By mathematical and experimental approaches, Bassel's team demonstrated that alternating temperatures act as an instructive signal in the root tip of Arabidopsis dormant seeds that define the distribution of hormone metabolites and ABA/GA transporter activity to break dormancy (Topham et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, shortly after imbibition, the daily temperature cycles might affect specific clock components that are linked to the regulation of dormancy and germination, rather than the overall performance of the circadian clock. In a dormancy cycling simulated experiment using clock mutants, Footitt et al () found that clock elements belonging to the central loop (i.e., CCA1, LHY, and TOC1) contribute to reduce the ABA sensitivity, and mutant seeds in these genes showed a faster entrance in secondary dormancy at 25 °C. In contrast, components of the clock belonging to the early loop (i.e., PRR5, PRR7, and PRR9) increased ABA sensitivity, and mutant seeds in PRR genes had a lower entrance in secondary dormancy.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, induction of primary dormancy was greatly influenced by the effect of maternal environments on embryo/endosperm Advances in Seed Biology [74,76,77] and/or on seed coat properties [78]. Dormancy intensity can be manipulated via controlling the daily circadian clock at reproduction [79]. Such effects can be passed down for multiple generations [80,81] and have been observed even in long-lived perennials, such as conifers [82].…”
Section: Seed Dormancymentioning
confidence: 99%